Optimizing Handover in Nursing Service Management at the Bulian Inpatient Ward of Bhayangkara Hospital - Yusnilawati, Yusnilawati; Kamariyah, Kamariyah; Sari, Putri Irwanti; Mawarti, Indah; Martawinarti, Rts Netisa; Oktaria, Rina; Mahendra, Syafira Nurliza (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2026)
Quality nursing care requires effective communication between healthcare workers, particularly during handovers, pre-conferences, and post-conferences. These three components are essential for nursing management to ensure continuity of care and patient safety. However, observations in the Bulian inpatient ward at Bhayangkara Jambi Hospital indicate that handovers and conferences have not been fully implemented, particularly in the application of effective communication techniques such as SBAR and consistent implementation according to standards. Therefore, a dissemination program was conducted to improve nurses' knowledge and skills in optimally implementing handovers, pre-conferences, and post-conferences.